2011
DOI: 10.1002/erv.1124
|View full text |Cite
|
Sign up to set email alerts
|

Disgust Sensitivity and Anorexia Nervosa

Abstract: Our findings elaborate on previous findings and are in line with recent neurological findings suggesting that disgust and insular impairments are associated with AN. Clinical implications of our findings are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 38 publications
1
39
0
1
Order By: Relevance
“…Aharoni and Hertz [44] demonstrated that individuals suffering from Anorexia Nervosa scored consistently higher on the Disgust Scale [30]. Therefore, we assessed participants’ risk of presenting an eating disorder by means of the EAT-26 [31].…”
Section: Discussionmentioning
confidence: 99%
“…Aharoni and Hertz [44] demonstrated that individuals suffering from Anorexia Nervosa scored consistently higher on the Disgust Scale [30]. Therefore, we assessed participants’ risk of presenting an eating disorder by means of the EAT-26 [31].…”
Section: Discussionmentioning
confidence: 99%
“…As with sensorial pleasures, research focused upon the significance of disgust in context of experiences of eating disorders is also relatively absent (Troop et al 2000;Warin 2010;Aharoni and Hertz 2012). While Aharoni and Hertz (2012) have found conclusively that eating disorders subjects have a higher sensitivity on a number of measures of disgust particularly in relation to bodily contagionthe contextualizing of disgust is in quantifiable terms -and misses the sensorial experiences that disgust evokes.…”
Section: Introduction: Mouthing Pleasure and Disgustmentioning
confidence: 92%
“…Potentially those affected by bulimia are much closer to the bodily encounters that may elicit feelings of self-disgust and shame due to the nature of bingeing and purging (Aharoni and Hertz 2012). In contrast, a person who is an anorectic who restricts food and does not binge and purge may feel the threat from disgusting images and ideas.…”
Section: Mouthing Disgust and Pleasure In Eating Disordersmentioning
confidence: 97%
See 1 more Smart Citation
“…Another non-specific vulnerability for women with concerns about their genitalia may be disgust sensitivity which is increased in women with dyspareunia or sexual dysfunction (Jong, van Overveld, Shultz, Peters, & Buwalda, 2009); and body image disorders such as anorexia nervosa (Aharoni & Hertz, 2012) or BDD (Neziroglu, Hickey, & McKay, 2010).…”
Section: Introductionmentioning
confidence: 99%